The The Problems of Gay Young Adults and Their Coping Strategies: An Exploratory Study - Pradanawan Febiansyah Nugraha; Nurchayati Nurchayati (Universitas Negeri Surabaya, 2023)
Using the case-study approach, this qualitative psychological research explores the problems of gay young adults and how they cope with them. Data for this study was collected through interviews with three young gay men. A thematic analysis of the resulting data revealed that these gay young adults wrestled with several problems, including discrimination, stigmatization, difficulty forming interpersonal relationships, and religious conflicts. To cope with the problems, they used emotion-focused and problem-solving strategies. This study concludes that effective coping strategies go a long way toward helping gay young adults to overcome life-challenges.